2020
DOI: 10.1177/2056305120939248
|View full text |Cite
|
Sign up to set email alerts
|

Follow Me Too: Determinants of Transitive Tie Formation on Twitter

Abstract: Transitivity, defined as the tendency for node A to be connected to node B given that A is connected to node X and X is connected to B, has been found to be a strong predictor of tie formation in various types of social networks. As transitive ties can influence information sharing, diffusion, and attitudes toward messages, understanding the motivations and mechanisms behind transitive tie formation in online social networks (OSNs) is important. Using a large longitudinal dataset from a popular OSN, Twitter, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Our arguments here are based on the concept of transitivity in network formation, which describes the tendency of actors who are connected to a third party to form mutual relationships over time (Batjargal, 2007;Granovetter, 1973). As previously noted, research has demonstrated that transitivity underlies tie formation in various network types (Batjargal, 2007;Carpenter, Esterling, & Lazer, 2004;Louch, 2000;Madhavan et al, 2004;Malik & Lee, 2020). Yet transitivity is by no means universal, and scholars have explained this variance by pointing to other underlying factors.…”
Section: Elite Transitivity and Interfirm Pipelinesmentioning
confidence: 97%
“…Our arguments here are based on the concept of transitivity in network formation, which describes the tendency of actors who are connected to a third party to form mutual relationships over time (Batjargal, 2007;Granovetter, 1973). As previously noted, research has demonstrated that transitivity underlies tie formation in various network types (Batjargal, 2007;Carpenter, Esterling, & Lazer, 2004;Louch, 2000;Madhavan et al, 2004;Malik & Lee, 2020). Yet transitivity is by no means universal, and scholars have explained this variance by pointing to other underlying factors.…”
Section: Elite Transitivity and Interfirm Pipelinesmentioning
confidence: 97%
“…For example, [15] argues that reciprocal relationships on social media cause emotional closeness between two users since they see each other's posts. Alternatively, reciprocity may signal two users are already friends or acquaintances [18]. Additionally, redundancy-either similar content to what the user follows or burst-tweeting-is a predictor of unfollowing [15,17].…”
Section: Unfollowing On Social Mediamentioning
confidence: 99%
“…Each and every aspect of it evolves non-stop and puts it on a higher position than radio, television, magazines, or even newspaper (Ohiagu, 2011). Internet media has the reach, ability to cover massive amount of target audience; simultaneity of reception, the ability to convey message instantly or at least nearly right away; anonymity, ability that enables people in communicating with anonymous audiences; heterogeneity of audience, ability to reach broad audience across sex, age, race, social class, culture, status, and location; and dual outreach, ability in being used for both mass reach and personal reach, enabling two-ways communication between the users (Malik & Lee, 2020).…”
Section: Introductionmentioning
confidence: 99%